PENGARUH HARGA DAN KERAGAMAN PRODUK TERHADAP MINAT BELI PADA KAGANGA COFFEE DI MAKASSAR - Vanes Viviana; Fitriani Latief; Nurhaeda Z (Jurnal Bisnis dan Kewirausahaan, 2023)
This study aims to determine (1) The effect of price and product variety partially on purchase intention at Kaganga Coffee in Makassar (2) The simultaneous effect of price and product variety on purchase intention at Kaganga Coffee in Makassar (3) Which variable has the most dominant influence on buying interest in Kaganga Coffee in Makassar. The sample of this research is 84 people who are customers of Kaganga Coffee. This study uses multiple linear regression analysis with data collection using a questionnaire with a Likert scale. The results of the study show that (1) Price and product variety partially have a significant effect on buying interest at Kaganga Coffee in Makassar (2) Price and product variety simultaneously have a significant effect on buying interest at Kaganga Coffee in Makassar (3) The most dominant variable influence on buying interest in Kaganga Coffee in Makassar is Product Diversity